Office workers health and injuries in government sector in the Statistic Departments of Malaysia, Muar, Johor Darul Ta'zim / Amiruddin Mohd Akhir, Muhamad Naim Gahnehman and Muhammad Danial Mahamud - Mohd Akhir, Amiruddin; Gahnehman, Muhamad Naim; Mahamud, Muhammad Danial (2012)
The purpose of this study is to determine the risks of health and injuries on office workers of Statistic Departments of Malaysia (Jabatan Perangkaan Malaysia), Muar,Johor Darul Ta'zim. This study also examines the safety level and the risks that faces by office workers of Statistic Departments of Malaysia, Muar, Johor Darul Ta'zim.All the information obtained wi II be collected through the questionnaire survey as the main instrument for this study. The questionnaires include 33 questions in all. It is divided into six questions in part A, 9 questions for each section B, C and D. Other than employee survey methods, researchers have also used the observation method. With this method, researchers can see the way the work done by employees and their behavior in the office. In this study are described on the factors of the accident or injury and the impact on employee's health consequences of not adopting the correct procedures when working. Survey questionnaires were distributed to employees in Statistic Department at Muar, Johor. A total of 40 respondents were selected to fill out these questionnaires. Workers involved range from subordinates such as clerks, general workers and so on. The mid-level managers such as supervisors also joined and high level employees such as department managers and branch directors are also involved.